Molecular mechanism and research progress on pharmacology of traditional Chinese medicine in liver injury - Hong Yang Zhang; Hong Ling Wang; Guo Yue Zhong; Ji Xiao Zhu (Taylor & Francis Group, 2018)
Context: Liver disease is a common threat to human health, caused by a variety of factors that damage the liver. Recent studies have shown that active ingredients (for example: flavonoids, saponins, acids, phenols, and alkaloids) from Traditional Chinese Medicine (TCM) can have hepatoprotective benefits, which represents an attractive source of drug discovery for treating liver injury. Objective: We reviewed recent contributions on the chemically induced liver injury, immunological liver damage, alcoholic liver injury, and drug-induced liver injury, in order to summarize the research progress in molecular mechanism and pharmacology of TCM, and provides a comprehensive overview of new TCM treatment strategies for liver disease. Materials and methods: Relevant literature was obtained from scientific databases such as Pubmed, Web of Science. and CNKI databases on ethnobotany and ethnomedicines (from January 1980 to the end of May 2018). The experimental studies involving the antihepatic injury role of the active agents from TCM and the underlying mechanisms were identified. The search terms included 'liver injury' or 'hepatic injury', and 'traditional Chinese medicine', or 'herb'. Results: A number of studies revealed that the active ingredients of TCM exhibit potential therapeutic benefits against liver injury, while the underlying mechanisms appear to contribute to the regulation of inflammation, oxidant stress, and pro-apoptosis signaling pathways. Discussion and conclusions: The insights provided in this review will help further exploration of botanical drugs in the development of liver injury therapy via study on the effective components of TCM.